Additive manufactured polymeric shock absorbers for automotive applications. Issue 11 (November 2022) - Riccio, A.; Madonna, M.; Palumbo, C.; Sellitto, A.
Abstract: This paper deals with the use of shock absorbers, placed in the upper roof of vehicles, able to increase the safety of passengers during an impact event. Numerical impact analyses have been introduced to demonstrate the effectiveness of these shock absorbers by assessing the deformations, stress and energy dissipation capabilities in the different structural components of a vehicle, somehow related to the safety of passengers. Indeed, shock absorbers have been found to play an important role in relation to passengers' safety. The homologation limitations of the reference regulation have been taken into account: FMVSS No. 201U "internal head impact – passenger compartment". This regulation, actually, provides a fundamental parameter, known as HIC(d) – "Head Injury Criteria", which is strictly related to the injuries of the passenger head under impact conditions alongside the rigid components inside the vehicle. The HIC(d) threshold value, if exceeded, affects the final conformity test of a vehicle. Hence, to fall within the range of reliable values of the HIC(d), shock absorbers need to be adopted. In order to increase these shock absorbers efficiency, in terms of passenger safety, in compliance with the regulations, the possibility of production of such devices by additive manufacturing techniques has been assessed. Abstract : Shock absorbers; Additive manufacturing; FEM; Automotive; Nonlinear model.